Charlie Chaplin the early years - Blades, Derek ([s.l] : RED Intertaiment, 1994)
Documented here is the deprived upbringing at the turn of the century of theyoung Charlie Chaplin, whose innate talents led him first into the music halls and West End theatres as a member of the great fred Karno's troupe
Keywords: Chaplin, Charles, 1889-1977; Comedians -- Great Britain -- Biography; Motion picture actors and actresses -- United States